SYNTHESIS OF AMINE-CONTAINING POLYMERIC MICROSPHERES BY SEED COPOLYMERIZATION FOR APPLICATIONS IN BIOTECHNOLOGY - A. V. Bakhtina; A. A. Sivaev; S. M. Levachev; S. A. Gusev; N. A. Lobanova; M. A. Lazov; I. A. Gritskova (Тонкие химические технологии, 2017)
This paper presents the results of studies of seed copolymerization of glycidyl methacrylate with ethylene glycol poly(glycidyl methacrylate) on seed particles in order to obtain partially crosslinked polymer microspheres with a diameter of about 3.5 microns for use in immunochemical reactions, as carriers of bioligands. The physico-chemical properties of polymeric microspheres obtained under different conditions were studied by the following methods: the diameters of the particles - by electron scanning and light microscopy; the wetting angle - bу the method of "lying droplets"; the sedimentation velocity - by the macromethod in a capillary tube by the movement of the (polymer slurry)/water phase boundary (buffer solution); the zeta-potential - by dynamic light scattering. Having studied the physical-chemical properties of all polymer slurries we concluded that the optimal particles to create on the basis of their diagnostic test systems with high sensitivity working on the principle of latex agglutination reaction are poly(glycidyl methacrylate) particles with equal percentage of glycidyl methacrylate and ethylene glycol dimethacrylate aminated with hexamethylendiamine in the environment of n-propanol, because they have a sufficient number of amino groups and do not lose their sedimentation properties after all stages of the synthesis.